2019
DOI: 10.1155/2019/2362618
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Epithelioid Angiomyolipoma Treated with Laparoscopic Resection: Case Report and Review of the Literature

Abstract: Hepatic angiomyolipoma is a rare primary liver tumor, with a radiographic appearance very similar to hepatocellular carcinoma. We present the case of a noncirrhotic patient with a liver tumor suspicious for HCC by imaging features. Liver biopsy demonstrated angiomyolipoma, and the patient successfully underwent a laparoscopic liver resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 11 publications
0
9
0
Order By: Relevance
“…Hepatic angiomyolipoma generally occurs in non‐cirrhotic livers, and patients lack serological abnormalities 4,11 . Cytological indicators include indistinct cell outlines (flowing appearance) and an absence of endothelial cells wrapping around hepatic trabeculae, a feature indicative of HCC 13,22 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hepatic angiomyolipoma generally occurs in non‐cirrhotic livers, and patients lack serological abnormalities 4,11 . Cytological indicators include indistinct cell outlines (flowing appearance) and an absence of endothelial cells wrapping around hepatic trabeculae, a feature indicative of HCC 13,22 .…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The well-known association between tuberous sclerosis complex (TSC) and AML is stronger in renal AML: 50%-80% of renal AMLs are found in conjunction with TSC, compared to only 5%-15% of HAML. [4][5][6] HAML, first reported in 1976, has remained a rare finding. 3,[7][8][9] Recent reviews in 2016 and 2018 estimate that approximately 600 cases of HAML have been reported to date.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In cases of HAML that require liver resection, laparoscopic hepatectomy could be a selective choice for surgical method. However, there have only been two reports about HAMLs that were removed using a laparoscopic procedure [ 9 ][ 9 ], and neither of these cases involved HAML that were misdiagnosed as other malignant liver tumors before surgery. Herein, we report 2 cases of HAML in which was removed by laparoscopic procedure after the preoperative diagnosis of other malignant tumor and was finally diagnosed as HAML depending on pathological findings of resected specimens.…”
Section: Introductionmentioning
confidence: 99%